2015
DOI: 10.1177/1203475415574946
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Clinical Scale for the Evaluation of Forearm Skin Photoaging

Abstract: A validated clinical photoaging scale for forearms with internal consistency, reliability, and validity was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
0
18
0
4
Order By: Relevance
“…The Institutional Review Board approved the study protocol, and consent form signatures were obtained. Subjects were divided into three groups according to their forearm skin photoageing degree, assessed by a validated clinical scale described below: Group 1 – light photoageing (score from 0 to 30); Group 2 –moderate photoageing (score from 31 to 70); and Group 3 – advanced photoageing (score from 71 to 100).…”
Section: Methodsmentioning
confidence: 99%
“…The Institutional Review Board approved the study protocol, and consent form signatures were obtained. Subjects were divided into three groups according to their forearm skin photoageing degree, assessed by a validated clinical scale described below: Group 1 – light photoageing (score from 0 to 30); Group 2 –moderate photoageing (score from 31 to 70); and Group 3 – advanced photoageing (score from 71 to 100).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the dorsal surface of the upper extremities is also exposed to similar levels of UV exposure. While exposure of skin to UV radiation promotes Vitamin D synthesis, chronic exposure causes photoage‐related degenerative changes that impact cellular, fibrous, and vascular skin structures . The cumulative effects of UV radiation on exposed skin surfaces have been shown to clinically manifest as elastotic skin changes, purpura, uneven skin pigmentation and melanoma and non‐melanoma skin lesions …”
Section: Discussionmentioning
confidence: 99%
“…While exposure of skin to UV radiation promotes Vitamin D synthesis, chronic exposure causes photoage-related degenerative changes that impact cellular, fibrous, and vascular skin structures. [47][48][49][50] The cumulative effects of UV radiation on exposed skin surfaces have been shown to clinically manifest as elastotic skin changes, purpura, uneven skin pigmentation and melanoma and non-melanoma skin lesions. [51][52][53][54][55][56][57][58] Despite a broad range of individual attributes, skin characteristics, and skin properties being assessed, this study may not have identified all factors that could contribute to the risk of skin tears.…”
Section: Discussionmentioning
confidence: 99%
“…A photographic assessment was obtained from two boarded dermatologists (blinded evaluators). The evaluation was based on the Guimarães scale, which analyses AK, lentigines, wrinkles, elastosis, elasticity, purpura and pseudostellar scars. Photographs were captured with Canon PowerShot G10 digital camera (Canon Inc., Tokyo, Japan) at OMNIA Imaging Station.…”
Section: Methodsmentioning
confidence: 99%